Determinants of Conjunctival Culture Positivity among Cataract Surgical Candidates: Impact of Diabetes and Demographic Factors - Dr Thakur Ankitha Singh; Dr Myla Satya Sindhu; Dr. Vootada Madhuri; Dr. Sara Sultana (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background While conjunctival flora is a known source of postoperative infections, the relative contribution of systemic and demographic variables to bacterial carriage before cataract surgery has not been comprehensively quantified. Methods Secondary analysis of a prospective cohort of 360 cataract patients (160 diabetics, 200 non-diabetics). Sociodemographic data, diabetes characteristics and ocular findings were recorded. Conjunctival cultures were categorised as positive or negative. Multivariate logistic regression identified independent predictors of culture positivity, and an additive risk-score model was constructed. Results Overall culture positivity was 47.8 %. Unadjusted analyses showed higher rates in diabetics (60.5 % vs 34.0 %), males (54.9 % vs 38.5 %) and patients ≥65 years (52.9 % vs 41.6 %). In the full model, diabetes (adjusted OR 2.76, 95 % CI 1.80-4.24), male sex (OR 1.68, 1.10-2.58), rural residence (OR 1.54, 1.01-2.36) and poor glycaemic control (HbA1c ≥ 8 %; OR 2.21, 1.28-3.82) remained significant. Each variable contributed one point to a four-item risk score that stratified culture-positivity probability from 23 % (0 points) to 78 % (≥3 points) (p-trend < 0.001). Conclusion Beyond diabetes, male gender and rural living independently predispose to conjunctival bacterial carriage before cataract surgery. A simple composite score may aid clinicians in identifying high-risk patients who warrant intensified prophylaxis.